HEALTH INEQUALITIES AND NON-COMMUNICABLE DISEASES IN UGANDA: A SYSTEMATIC REVIEW. - Kajubi , Richard; Malik, Koire; Alimwenda, Violet; Ali , Anahita (Student's Journal of Health Research Africa, 2024)
Background Non-communicable diseases (NCDs), including cardiovascular diseases, cancers, chronic respiratory diseases, and diabetes, are leading causes of death worldwide, particularly affecting low— and middle—income countries (LMICs). This study systematically reviews the extent of health inequalities in NCDs across various demographic groups in Uganda. Methodology This systematic review employed the PICO framework and followed standardized international protocols for data extraction and quality assessment. Comprehensive searches were conducted across PubMed and Web of Science databases, yielding 296 and 106 initial records from the databases respectively. After screening and applying inclusion criteria, 53 studies were included for qualitative synthesis. Data extraction focused on study characteristics, population demographics, interventions, outcomes, and key findings. Methodological quality was appraised to ensure validity, accuracy, and generalizability. Results The review highlights significant disparities in NCD prevalence across different demographic groups in Uganda. Notably, the elderly population in rural areas shows a high prevalence of NCDs, influenced by factors such as poor housing conditions, limited physical activity, and inadequate kitchen ventilation. Individuals living with HIV (PLHIV) exhibit compounded health burdens, with hypertension being a common comorbidity. Urban-rural disparities in NCD prevalence are evident, with lifestyle factors associated with urbanization contributing to increased risks. Alarmingly, mortality rates attributable to NCDs, particularly cardiovascular diseases and diabetes, have risen over the past decade. Barriers to healthcare access, including geographic, financial, and policy—related challenges, exacerbate these disparities. Conclusion Among the elderly population residing in rural areas, a strikingly high prevalence of NCDs is observed, influenced by factors such as substandard housing conditions, limited physical activity, and inadequate kitchen ventilation. This underscores the urgent need for targeted interventions aimed at improving living conditions and promoting healthy behaviors among this vulnerable demographic group. Recommendation Further research is warranted to explore the underlying determinants of these disparities in greater depth.